TRADISI RAMBU TUKA' SEBAGAI EKSPRESI LITURGI SUKACITA DALAM PEMBENTUKAN SPIRITUALITAS KRISTEN MASYARAKAT TORAJA: TINJAUAN BERDASARKAN MAZMUR 100 DAN PEMIKIRAN ROBERT E. WEBBER TENTANG WORSHIP - Yobel; Firmawati; Feby Ade Santia Kinda; Renianti Lara; Marselina Seppang (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study analyzes Rambu Tuka' as an expression of joyful liturgy in the formation of Christian spirituality among the Toraja people based on Psalm 100 and Robert E. Webber's thought on worship. The main problem addressed is the neglect of Rambu Tuka' in Christian Education discussions despite its rich liturgical and spiritual dimensions, as well as the tendency of Toraja churches to overemphasize seriousness and formality in worship, marginalizing the biblical dimension of joy. The research employs a qualitative approach with descriptive-analytical library research methods, analyzing Psalm 100 through exegesis, Webber's concept of ancient-future worship, and descriptions of Rambu Tuka' practices in related literature. The findings show that Rambu Tuka' has strong resonance with principles of joyful liturgy in Psalm 100 and Webber's thought, encompassing responsorial, corporate-participatory dimensions, total self-involvement, and spiritual progressivity. Liturgical elements of Rambu Tuka' such as communal celebration, music, dance, and thanksgiving offerings can be integrated into Christian worship through careful theological transformation. This integration implies the development of balanced contextual liturgy, transformation of offering meanings, and creation of natural Christian Education learning contexts for younger generations, thereby enriching Toraja Christian spirituality holistically and biblically.